Reduction of large circuit models via low rank approximate gramians - Li, Jing-Rebecca; White, Jacob (Zielona Góra: Uniwersytet Zielonogórski)
We describe a model reduction algorithm which is well-suited for the reduction of large linear interconnect models. It is an orthogonal projection method which takes as the projection space the sum of the approximate dominant controllable subspace and the approximate dominant observable subspace. These approximate dominant subspaces are obtained using the Cholesky Factor ADI (CF-ADI) algorithm.
Keywords: model reduction; Lyapunov equations; Cholesky-Factor ADI; moment matching; passivity